The Molecular Biology, Biochemistry, and Physiology of Human Steroidogenesis and Its Disorders - Miller, Walter L.; Auchus, Richard J. (Endocrine reviews, 2011)
Steroidogenesis, the processes by which cholesterol is converted to steroid hormones, involves transport proteins, enzymes, redox partners and cofactors. Most steroidogenic enzymes are either forms of cytochrome P450 or are hydroxysteroid dehydrogenases. The P450s may be either Type 1, in mitochondria, or Type 2, in the endoplasmic reticulum; these two types differ in their electron-transfer redox partners as well as in their cellular locations. Hydroxysteroid dehydrogenases may be either shortchain dehydrogenases or aldo-keto reductases, which differ in their structures and catalytic mechanisms. Recent work has identified new enzymes, co-factors and protein modifications, and has described new pathways of steroidogenesis and new sites of steroid synthesis. Thus steroidogenesis is not confined to the adrenals and gonads, and involves more than the production of aldosterone, cortisol and sex steroids. We review the enzymes, factors and pathways of human steroidogenesis and the diseases resulting from their mutations.Steroidogenesis entails processes by which cholesterol is converted to biologically active steroid hormones. Whereas most endocrine texts discuss adrenal, ovarian, testicular, placental, and other steroidogenic processes in a gland-specific fashion, steroidogenesis is better understood as a single process that is repeated in each gland with cell-type-specific variations on a single theme. Thus, understanding steroidogenesis is rooted in an understanding of the biochemistry of the various steroidogenic enzymes and cofactors and the genes that encode them. The first and rate-limiting step in steroidogenesis is the conversion of cholesterol to pregnenolone by a single enzyme, P450scc (CYP11A1), but this enzymatically complex step is subject to multiple regulatory mechanisms, yielding finely tuned quantitative regulation. Qualitative regulation determining the type of steroid to be produced is mediated by many enzymes and cofactors. Steroidogenic enzymes fall into two groups: cytochrome P450 enzymes and hydroxysteroid dehydrogenases. A cytochrome P450 may be either type 1 (in mitochondria) or type 2 (in endoplasmic reticulum), and a hydroxysteroid dehydrogenase may belong to either the aldo-keto reductase or short-chain dehydrogenase/reductase families. The activities of these enzymes are modulated by posttranslational modifications and by cofactors, especially electron-donating redox partners. The elucidation of the precise roles of these various enzymes and cofactors has been greatly facilitated by identifying the genetic bases of rare disorders of steroidogenesis. Some enzymes not principally involved in steroidogenesis may also catalyze extraglandular steroidogenesis, modulating the phenotype expected to result from some mutations. Understanding steroidogenesis is of fundamental importance to understanding disorders of sexual differentiation, reproduction, fertility, hypertension, obesity, and physiological homeostasis.